Analisis Terhadap Pembulatan Timbangan Pengiriman Barang pada JNE Menurut Persepektif Hukum Islam - Nazar, Taufid Hidayat (Institut Agama Islam Negeri Metro, 2022)
In the highly competitive courier service industry, PT. JNE Express strives to position itself as a leading provider of quality delivery services. To achieve this, the company must understand the factors that influence customer satisfaction. PT. JNE Express is well-known among business operators in Indonesia due to its extensive network of agents across provinces, districts, cities, and sub-districts. JNE applies a weight-based system for shipping charges, where the weight of the package is rounded up to the nearest kilogram. For example, a package weighing 1.4 kg is rounded up to 2 kg. This study examines whether the rounding practice in PT. JNE Express' shipping charges disadvantages consumers and how Islamic law views this practice. The findings suggest that the rounding practice may potentially harm consumers by charging them for a higher weight than the actual weight of the package, leading to unjust financial burdens. From an Islamic legal perspective, such practices may be seen as unfair and inconsistent with the principles of fairness and transparency in business transactions. The study concludes that while Ijarah contracts are permissible in Islam, the practice of rounding up without clear justification may need reform to align with Islamic economic principles of justice and consumer protection.